PENGEMBANGAN FLIPBOOK OF KHULAFAURRASYIDIN LEADERSHIP SEBAGAI MEDIA UNTUK MEMAHAMI POLITIK ISLAM BAGI ANAK SEKOLAH DASAR - Iya Riyani; Utari Utari; Wanty Cahyanti; Ani Nur Aeni (Prodi PGMI STIT Sunan Giri Bima, 2022)
Along with the changing times that are increasingly advanced, namely with the development of increasingly sophisticated technology, the younger generation today is fast in learning the technology. Then, this research has a purpose as a means of information related to politics in an Islamic perspective to the younger generation, especially elementary school children by spurring the example and characteristics of Khulafaurrasyidin which is published in the form of a Flipbook in order to adapt to the changing times that are happening at this time, namely by take advantage of technology. In addition, this study uses a qualitative method using questionnaires and interviews. We use this technique for teachers and students. We conducted these questionnaires and interviews with teachers and students. This research also uses the Design and Development (D&D) model. Regarding the process of making the video